COMMUNITY BASED TOURISM FESTIVALS IN THE MÉDIO TEJO REGION, PORTUGAL A POTENTIAL FOR THE SPECIALIZED CULTURAL CONSUMPTION OF CREATIVE TOURISM - Carvalho, Rui (2019)
Submitted by Domingos Martinho (domingos.martinho@islasantarem.pt) on 2019-06-25T00:27:54Z No. of bitstreams: 1 Carvalho,Costa & Ferreira, 2015.pdf: 1249450 bytes, checksum: cf7c1aed888b13f91e0c5d8c87b89e3d (MD5)